EXPLORING EDUCATIONAL TECHNOLOGY INTEGRATION IN CAMBODIAN HIGHER EDUCATION: CHALLENGES AND OPPORTUNITIES - Keo, Vireak; Lan, Bunrosy (The Journal Of English Teaching For Young And Adult Learners, 2025)
This literature review explores the challenges and opportunities associated with integrating educational technology in Cambodian higher education institutions. It aims to identify effective strategies for incorporating technology into teaching and learning. By systematically analysing research studies, academic publications, and empirical data from 2007 to 2023, the review highlights key obstacles, including technical limitations, restricted access to digital tools, cultural barriers, insufficient digital literacy, high costs, and inadequate infrastructure. Conversely, educational technology offers numerous benefits, such as increased student engagement, access to diverse learning resources, support for self-directed learning, and the development of essential 21st-century skills. Additionally, it facilitates global communication, enriching the overall educational experience. The findings indicate that successfully integrating technology into Cambodian higher education requires addressing these challenges while maximizing the available opportunities. To achieve this, school administrators must enforce institutional and classroom policies to prevent the ineffective use of digital tools, ensuring that both educators and students gain meaningful educational benefits.